Metallochelating liposomes with associated lipophilised norAbuMDP as biocompatible platform for construction of vaccines with recombinant His-tagged antigens: preparation, structural study and immune response towards rHsp90 - Mašek, Josef; Bartheldyová, Eliška; Turánek-Knotigová, Pavlína; Skrabalová, Michaela; Korvasová, Zina; Plocková, Jana; Koudelka, Stěpán; Skodová, Petra; Kulich, Pavel; Křupka, Michal; Zachová, Kateřina; Czerneková, Lýdie; et al. (Journal of controlled release, 2011)
Hsp90-CA is present in cell wall of Candida pseudohyphae or hyphae-typical pathogenic morphotype for both systemic and mucosal Candida infections. Heat shock protein from Candida albicans (hsp90-CA) is an important target for protective antibodies during disseminated candidiasis of experimental mice and human. His-tagged protein rHsp90 was prepared and used as the antigen for preparation of experimental recombinant liposomal vaccine. Nickel-chelating liposomes (the size around 100nm, PDI≤0.1) were prepared from the mixture of egg phosphatidyl choline and nickel-chelating lipid DOGS-NTA-Ni (molar ratio 95:5%) by hydration of lipid film and extrusion methods. New non-pyrogenic hydrophobised derivative of MDP (C18-O-6-norAbuMDP) was incorporated into liposomes as adjuvans. rHsp90 was attached onto the surface of metallochelating liposomes by metallochelating bond and the structure of these proteoliposomes was studied by dynamic light scattering, AF microscopy, TEM and GPC. The liposomes with surface-exposed C18-O-6-norAbuMDP were well recognised and phagocyted by human dendritic cells in vitro. In vivo the immune response towards this experimental vaccine applied in mice (i.d.) demonstrated both TH1 and TH2 response comparable to FCA, but without any side effects. Metallochelating liposomes with lipophilic derivatives of muramyl dipeptide represent a new biocompatible platform for construction of experimental recombinant vaccines and drug-targeting systems.
Keywords: dendritické buňky; kultivované buňky; biokompatibilní potahované materiály; syntetické vakcíny; antigeny fungální; myši; HSP90 Heat-Shock Proteins; Antigens, Fungal; Immunity, Cellular; Humans; Vaccines, Synthetic; Candida; Chelating Agents; zvířata; ženské pohlaví; Dendritic Cells; Nickel; Female; proteiny tepelného šoku HSP90; Animals; Mice; nikl; liposomy; Coated Materials, Biocompatible; Mice, Inbred BALB C; Liposomes; buněčná imunita; Cells, Cultured; lidé; chelátory; myši inbrední BALB C